Bringing class diagrams to life - Barbosa, L. S. (2010)
Research in formal methods emphasizes a funda- mental interconnection between modeling, calculation and prototyping, made possible by a common unambiguous, mathematical semantics. This paper, building on a broader research agenda on coalgebraic semantics for Unified Modeling Language diagrams, concentrates on class diagrams and discusses how such a coalgebraic perspective can be of use not only for formalizing their specification, but also as a basis for prototyping.